Basic Literacy Skills of Vocational High School Students Based on Their Perceptions - Muhammad Hudan Rahmat; Sukardi Sukardi; Debora Debora; Ratna Pancawati (PAEDAGOGIA, 2025)
Literacy in vocational high schools (VHS) plays an important role in improving the quality and success of graduates to be ready to face the world of technology-based work. However, the lack of literacy is still a major challenge for VHS students. This study aims to (1) describe the basic literacy skills of VHS students based on their perceptions, and (2) identify weaknesses in the basic literacy skills of VHS students. This study uses a descriptive quantitative approach. The sample consisted of 134 students from mechanical and automotive engineering vocational programs. Data collection was conducted using a closed questionnaire as an instrument.  Then, the collected data is analyzed using descriptive statistics. The research results show that (1) the majority of vocational school students' literacy skills are at a moderate level, namely reading and writing 59.7%, numeracy 64.9%, science 69.4%, digital 67.9%, and culture 51.5%. (2) Among these, the lowest scores were in numeracy, with an average score of 63.89. This confirms that VHS students perceive numeracy as a different challenge and irrelevant to their field. This finding could be due to the limited integration of numeracy concepts into vocational learning; improvement of numeracy skills in vocational settings is essential to enhance students' abilities in technical fields. For future research, combining test-based evaluation with reported surveys would be more complete to obtain a more precise and objective assessment of literacy competency among VHS students. In addition, further research needs to explore the role of teaching methods and examine the impact of digital learning media on their literacy performance, especially in numeracy skills.